الألفاظُ المُعَرَّبة في فتح الباري بشرح صحيح البخاري لإبن حجر العسقلاني (Journal of the College of Education for Women, 2019)
This research deals with a range of vocabulary, non-Arab, whichappeared in a book Fath al-Baari by Ibn Hajar al-Askalani, so we display thisvocabulary and matrix is scholarly tuned in, interpretation and statement oforigin, and then matrix is what I'm stone in the view of the scientists and wasfor Ibn Hajar outstanding efforts in the follow-up statements The scientistsdocumented a valuable book and it is fath Al-Bari important source ofvocabulary Aloagamip the complexity and multiplicity of views.